Cadherin 2 is Required for Intervertebral Disc Homeostasis and Maintenance of Vacuolated Phenotype in Nucleus Pulposus Cells. (May 2014) - Lim, F.; Tam, W. K.; Au, T. Y.; Chan, D.; Cheah, K. S.; Tuan, R. S.; Cheung, K. M.; Leung, V. Y.
Introduction: Integrity of the nucleus pulposus (NP) has been implicated in the function and homeostasis of intervertebral disc (IVD). Understanding the regulation of NP cells would contribute to their engineering and development of therapeutics for treating IVD degeneration. Studies in mouse models indicate that early events of IVD degeneration involve segregation of the notochordal NP cell clusters, 1 suggesting that disc degeneration may be associated with cell adhesion molecule activities. Cadherins are transmembrane glycoproteins that mediate calcium dependent cell adhesion. 2 Based on microarray analysis, we have revealed specific expression of Cdh2 gene, encoding cadherin 2/N-cadherin, in rodent NP cells, suggesting a potential regulatory role of cadherins in IVD homeostasis. To date, the function of cadherin 2 in IVD and its relationship to IVD degeneration remain elusive. We hypothesize that cadherin 2 has a regulatory role in NP cells and that a deregulation of its activities has adverse effects on IVD homeostasis. We aimed to study the expression pattern of cadherin 2 in rodent discs during development, aging, and degeneration, and to investigate its function in the NP via a gene and protein ablation strategies. Materials and Methods: Animal experiments were approved by local ethics committee. The vertebral columns of wild-type C57BL/6N mice were collected at different ages ( n = 4): embryonic day (E) 12.5, E14.5, postnatal day 0 (P0), 3 months old, 6 months old, 1 year old, 1.5 and 2 years old. Progressive disc degeneration was induced by annulus puncture of 4-month-old inbred Lewis rats ( n = 6) with 25G needle, and the discs were harvested after 2-, 4-, and 8-weeks of operation. Lumbar IVD of scoliosis patients and lower lumbar spine of the aborted fetus in the second trimester were used as controls. Immunohistochemistry was performed on paraffin sections to study the cadherin 2 expression pattern. For protein ablation study, 4-month-old inbred Lewis rats were anesthetized and the tail IVDs were exposed for injection of rabbit anti-cadherin 2 antibody or control rabbit IgG ( n = 6) into the NP via 34G hypodermic needle. Cadherin 2 gene (Cdh2) was knocked out in the NP using notochord-specific Foxa2-Cre recombination strategy. Disc height was measured and expressed as disc height index (%DHI). The IVD were harvested by 2 and 8 weeks after operation (protein ablation) and from P0 and 1 month-old mutants (gene knockout) for histological analysis. Results: By immunofluorescence, cadherin 2 was weakly detected in murine embryonic notochord and newborn NP. At 3- and 6-month old, strong cadherin 2 signals were specifically detected as foci along the cell-cell junctions of the vacuolated NP cells (notochordal cells). Annulus fibrosus showed no signals. In aged IVD, the notochordal cells were replaced by small chondrocyte-like cells with lower expression of cadherin 2. In puncture-induced degenerative rodent discs, the notochordal NP cells were replaced by rounded chondrocyte-like cells, showing reduced level of cadherin 2 expression. Human NP showed heterogeneous cadherin 2 expression. By injecting cadherin 2 antibody into rat NP to perturb its function in vivo, cadherin 2 expression was reduced along with reduction of disc height. Compared with the IgG injection control, cadherin 2 antibody ablation group showed a transformation of the notochordal NP cells into less vacuolated chondrocyte-like phenotype with upregulation of collagen II. Cdh2 conditional knockout mice (CKO) showed absence of cadherin 2 and a loss of vacuolated phenotype in the NP cells (Fig. 1A), displaying significantly smaller body size by 1-month old (Fig. 1B). Moreover, the mutant exhibited irregular annulus organization and reduced disc height in IVD (V). Conclusion: Our study suggests cadherin 2 as a marker of notochordal NP cells. The lower expression of cadherin 2 in the aged and puncture-injured rodent IVD substantiates its association with IVD degeneration. The reduction of cadherin 2 positive NP cells in mature human IVD is consistent with gradual loss of notochordal cells after the first decade of life. Our parallel in vivo studies of gene/protein ablation support that cadherin 2 is essential to the maintenance of a vacuolated phenotype of the notochordal NP cells, and that a loss of cadherin 2 function may initiate degenerative changes in the IVD. In summary, our study implicates an important role of cadherin 2 in notochordal cell function and regulating IVD homeostasis. Acknowledgments This work is funded by the Area of Excellence grant (AoE/M-04/04) and the General Research Fund (HKU763712M) from the Research Grant Council of Hong Kong. Disclosure of Interest None declared References Yang F, Leung VY, Luk KD, Chan D, Cheung KM. Injury-induced sequential transformation of notochordal nucleus pulposus to chondrogenic and fibrocartilaginous phenotype in the mouse. J Pathol 2009;218(1):113–121 Leckband D, Prakasam A. Mechanism and dynamics of cadherin adhesion. Annu Rev Biomed Eng 2006;8:259–287